Pink Floyd y su importancia cultural: un tríptico - Boza Méndez, David (2015)
This article shows, through a testimony-like narration, some of the reasons why the music of Pink Floyd is believed to have a cultural significance. Furthermore, the essay presents the analysis of some of the most remarkable themes in three albums of the band.